Effect Of Silica Fume On The Properties Of Hollow Concrete Block - Nordin, Nuratikah Ahmad (Universiti Sains Malaysia, 2019)
Concrete block has been commonly used in constructions since in the first half of the 20th century. The blocks are mainly used as fillers in wall constructions and also as load bearing units. Since the demand of concrete block is high on the market currently and possibly the future, this study is done to find the properties of concrete block especially hollow concrete block with other materials in order to enhance its performance and durability. For this research, hollow concrete block with an admixture of silica fume was formed by using a dry mix design ratio, 1:6. Tests such as compressive strength test, density test, water absorption test and initial rate of suction (IRA) were done to find the properties of the block and to compare them to the control block that was also created by using the same dry mix design ratio but without any admixture. A total of 36 samples were produced for both the control block and the block with silica fume. The properties of the hollow concrete blocks were taken based on the testing results. From the results and observations, the strength of the hollow concrete block with silica fume was enhanced and higher than the control block by approximately 50%. The water absorption and initial rate of suction of the silica fume concrete block were also lower than the control, and the blocks were much denser.